Peran Administrasi Digital dalam Pengelolaan Startup Mahasiswa pada Era Transformasi Teknologi - Yulianti Toralawe; Neva Lionitha Ibrahim; Imam Prawiranegara Gani (Journal of Management and Creative Business, 2026)
Digital transformation has encouraged the emergence of student startups that utilize technology to support business operations and service delivery. However, studies specifically examining the role of digital administration in managing student startups remain limited, as previous research has primarily focused on business innovation and digital marketing. This study aims to analyze the role of digital administration in the management of student startups in the era of technological transformation. A descriptive qualitative approach was employed through structured interviews with five student startup managers. The findings reveal that digital administration contributes significantly to data management efficiency, administrative service speed, information accuracy, information accessibility, and work productivity. The use of websites, social media, and cloud-based services enables startups to manage information systematically, improve service quality, and enhance operational effectiveness. The study implies that universities should strengthen students’ digital administration competencies through training, mentoring, and digital infrastructure support to foster innovative, sustainable, and competitive student startups.